2009
DOI: 10.1016/j.jcv.2009.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpes viruses in children with acute appendicitis

Abstract: AbstractsOf all the specimens, the omentum was the most commonly infected tissue (63.0%) while the appendix and peripheral blood specimens were found to be positive for viral infection in 60.5% and 50% of cases, respectively. The CMV IgG+ antibodies were positive in 54% of the control cases while 86% of the same group presented HHV-6 IgG+ antibodies. Conclusion To the best of our knowledge, this is the first study documenting the presence of herpes virus DNA in children with acute appendicitis, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 32 publications
0
15
0
1
Order By: Relevance
“…There has been a long standing suspicion that non-HHV viral infections are associated with appendicitis, given it’s bimodal and seasonal occurrence (158). The first described association of HHV with appendicitis was in an AIDS patient (159), but a recent study of childhood appendicitis has shown periodic reactivation (21%) of CMV in lymphoid tissue of the appendix (160). In this study, HHV-6 was also identified in about 8% of specimens.…”
Section: Virusesmentioning
confidence: 99%
“…There has been a long standing suspicion that non-HHV viral infections are associated with appendicitis, given it’s bimodal and seasonal occurrence (158). The first described association of HHV with appendicitis was in an AIDS patient (159), but a recent study of childhood appendicitis has shown periodic reactivation (21%) of CMV in lymphoid tissue of the appendix (160). In this study, HHV-6 was also identified in about 8% of specimens.…”
Section: Virusesmentioning
confidence: 99%
“…4 HHV-6'nın akut apandisit ve aortta kronik arterite yol açtığına dair yayınlar da bildirilmiştir. 26,27 Ayrıca, HHV-6 reaktivasyonu ile skleroderma arasında güçlü bir ilişki olduğu öne sürülmekte-dir. 28 HHV-6 için tanısal testler seroloji, kültür, immünohistokimya ve nükleik asit incelemelerinden ibarettir.…”
Section: Human Herpes Vi̇rüs-6unclassified
“…The presence of bacteria within the peritoneal cavity during inflammatory processes was demonstrated at the beginning of the past century and the bacteria involved have been subsequently found, the most common ones being Escherichia coli, followed by Klebsiella pneumoniae, Streptococcus species, Enterococcus species and Pseudomonas aeruginosa. 1,2 This led to the adjustment of post-operative empirical antibiotic treatment, [3][4][5][6][7][8][9][10] although with the advent of broad spectrum antibiotics, routinary microbiological cultures of abdominal fluid specimens lost most of their importance. 11,12 Moreover, a specific disadvantage of cultures was that both pathogen identification and antibiotic sensitivity results were often available only after patients discharge.…”
Section: Introductionmentioning
confidence: 99%